Suárez and Leibniz on principles - Pereda, Rubén (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
G. W. Leibniz was a regular reader of the philosophical work of Suárez, reading that left a deep trace in his metaphysics. Specifically, Leibniz’s use of the principles can be considered a practical application of Suárez’s approach regarding principles in the Metaphysical Disputations.